Study guides

☆☆

Q: What does k plus f plus s plus t plus f plus f equals g of an ES?

Write your answer...

Submit

Still have questions?

Related questions

No, by itself it is not.

f(x)=x+1 g(f(x))=x f(x)-1=x g(x)=x-1

g(x) = 5. So whatever f(x) or f(-1) is, g of that is going to be 5.

g(x) = x + 3 Then f o g (x) = f(g(x)) = f(x + 3) = sqrt[(x+3) + 2] = sqrt(x + 5)

x = 75

=b+2h+r+x+z+q+a+p+l+f+g+d

Let f ( x ) = 3 x 5 and g ( x ) = 3 x 2 4 x

578392g

f = 54

f/a equals pressure.

f and g are inverse functions.

No, they are not equivalent.

=2969726895655+g+f+k+x

gf(5) = g(f(5)) = g(5+1) since f(x) = x+1 and then g(6) = 3*6 - 2 = 18 - 2 = 16

Addition is commutative.

the formula for balanced forces is M times G plus F equals balanced forces

d/dx [f(x) + g(x)] = d/dx [f(x)] + d/dx [g(x)] or f'(x) + g'(x) when x = 3, d/dx [f(x) + g(x)] = f'(3) + g'(3) = 1.1 + 7 = 8.1 d/dx [f(x)*g(x)] = f(x)*d/dx[g(x)] + d/dx[f(x)]*g(x) when x = 3, d/dx [f(x)*g(x)] = f(3)*g'(3) + f'(3)*g(3) = 5*7 + 1.1*(-4) = 35 - 4.4 = 31.1

2d+2h+2t+g+f+2r+w+x

Yes

-2

g=12

1 foot in the grave.

z remains undefined.

1 plus one

if 'g' = minus 3 then 20 + -3 = 17 17 + -3 = 14